Watching TV Through Your Ears: An Overview of Catalan-language Broadcasters’ Accessibility Services Offered for Viewers With Sight Loss - Tor-Carroggio, Irene; Rovira-Esteva, Sara (Journal of Audiovisual Translation, 2020)
Since 2010 the provision of audio description is legally required on TV in Spain. The objective of this study was threefold: to investigate the current state of the media accessibility services of Catalan-language broadcasters for viewers with sight loss in relation to current legislation; to assess user satisfaction with these services; and to gather feedback from users on non-professional services. According to our results broadcasters fail to comply with the law in terms of quantity, although users are fairly satisfied with the quality offered and are willing to explore new approaches for AD provision.